Propaganda as a system-forming element of education in authoritarian countries: problems of understanding - Микита Шпильовий (Філософія освіти)
Modern Ukrainian society is faced with a threat that democratic political regimes could not imagine before. Propaganda, disinformation, informational and psychological operations and countermeasures have become familiar activities for Ukrainians. Today, we often analyze certain challenges and in some sense society has already adapted to them and learned to respond to new challenges according to a certain system. However, the very definition of propaganda and the principle of its action remains a blurred problem for society and it is covered from the standpoint of journalism rather than science. Even despite the rather urgent need to scientifically analyze and respond to informational challenges, today’s Ukrainian scientific opinion has little to offer to this struggle. An even bigger mystery for us is the question of why the propaganda worked at all, and how did it happen that we did not notice it for years? Why, despite all the principles of common sense, propaganda can work as a tumbler that fundamentally changes not only how a person understands this or that concept, but also distorts the thinking paradigm and fundamentally changes the picture of the world and political orientations. This work provides a broad understanding of the concept of propaganda, how it works and affects society, what methods propaganda authors use, and why education is one of the most important elements of propaganda in modern autocratic countries. In the end, the article consistently proves that some political regimes do not make propaganda an element of education, but education an element of propaganda, subordinating the entire individual human life to artificial and controlled thinking principles. The article relies on classic philosophical works that are tangential to the topic of propaganda and extensively analyzes the mass media in order to compare facts and images to build a complete picture of a living intellectual organism, which we call propaganda.